Hubungan antara Regulasi Emosi dengan Kecenderungan Self-Injury pada Remaja di Kabupaten Sorong - Ningrum, Ayu Reksanti Mutiara; Wahyuni, Nengsih Sri; Ekayani, Syafira Putri (Universitas Muhammadiyah Metro, 2024)
Emotion regulation is a person’s ability to recognize, manage, and evaluate a person’s emotions. Self-injury is an activity that takes out negative feelings within a person to hurt oneself. This research aims to find out whether there is a relationship between emotional regulation and the tendency to self-injury in adolescents in Sorong Regency. This research used a correlation quantitative approach with 15 students as subjects. The method for taking subjects used the snowball technique with the Pearson Product Moment data analysis technique. The data obtained was analyzed using statistics from the SPSS (Statistical Program for Social Science) for Windows Release version 25.0 program. Based on the result of the analysis, there is a significant negative relationship between emotional regulation and self-injury tendencies in Senior High School in the 2nd grade has a correlation coefficient value of (-0,718) with a substantial value of (sig.) 0.003 (p0.05), thus it can be concluded that the higher the emotional regulation, the lower the tendency to self-injury, and vice versa.